1998
DOI: 10.1046/j.1472-765x.1998.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase release assay to determine cytotoxicity for Listeria species

Abstract: A .K . B H UN IA A ND D. G . W ES T BR OO K . 1998. A simple cytotoxicity assay for Listeria species was developed by assaying alkaline phosphatase (AP) release from an infected hybrid B lymphocyte (Ped-2E9) line. Eight of eight L. monocytogenes and six of 11 L. ivanovii strains induced significantly high AP release from Ped-2E9 cells compared to five other L. ivanovii strains and other Listeria spp. In contrast, all L. monocytogenes and L. ivanovii test strains showed high release of lactate dehydrogenase (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…The cytotoxicity effects of bacterial cells or the toxin preparations on collagen-encapsulated Ped-2E9 cells were measured by an ALP release assay as described previously. 40 Briefly, 50-100 ml of bacteria cell suspension (1 Â 10 9 CFU/ ml) or crude toxin preparations (B20 mg/ml, 50-100 ml) were added to each well of the 96-or 48-well microtiter plate, respectively, and held at 371C in a humidified incubator with B cells in gel as biosensors P Banerjee et al 7% CO 2 for a period of 3-6 h. The supernatant from the 48-well plate was collected, centrifuged (1800 g for 5 min) and placed in a mini-cuvette containing a ready-to-go ALP liquid substrate (Sigma). The color development was recorded at 3-5 min intervals at absorbance of 405/595 nm using a handheld USB2000 mini-spectrophotometer (Ocean Optics, Dunedin, FL, USA).…”
Section: Measurement Of Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity effects of bacterial cells or the toxin preparations on collagen-encapsulated Ped-2E9 cells were measured by an ALP release assay as described previously. 40 Briefly, 50-100 ml of bacteria cell suspension (1 Â 10 9 CFU/ ml) or crude toxin preparations (B20 mg/ml, 50-100 ml) were added to each well of the 96-or 48-well microtiter plate, respectively, and held at 371C in a humidified incubator with B cells in gel as biosensors P Banerjee et al 7% CO 2 for a period of 3-6 h. The supernatant from the 48-well plate was collected, centrifuged (1800 g for 5 min) and placed in a mini-cuvette containing a ready-to-go ALP liquid substrate (Sigma). The color development was recorded at 3-5 min intervals at absorbance of 405/595 nm using a handheld USB2000 mini-spectrophotometer (Ocean Optics, Dunedin, FL, USA).…”
Section: Measurement Of Cytotoxicitymentioning
confidence: 99%
“…16,37,38 This cytotoxicity assay can also differentiate the presence of viable pathogenic Listeria species from nonpathogenic ones. 16,[39][40][41][42] Adherent and nonadherent mammalian cell lines of various tissue origins were used previously to distinguish differential cytotoxic response of virulent Listeria species from avirulent ones. 16,[43][44][45] The cytotoxic properties were determined by monitoring the changes in cell morphology, 42 formation of plaques in a monolayer, 43,45 or dye uptake due to loss of membrane permeability.…”
mentioning
confidence: 99%
“…3). Similarly, in the AP assay, strains AAMU530 and AAMU572 induced AP releases of 16 and 15% respectively, which was significantly lower than the ) release from Ped-2E9 cells [32]. Percentage cytotoxicity was determined based on the total alkaline phosphatase (AP) release from Triton-Xtreated Ped-2E9 cells.…”
Section: Cytotoxicity Projile Of Mutant Strainsmentioning
confidence: 99%
“…In order to make the Ped-2E9 assay a rapid and sensitive one, reducing agent DTT in the cell suspensions were added to enhance L. monocytogenes mediated cell cytotoxicity. Data presented here showed that DTT added to the listerial cells or its culture supernatants can augment the cytopathogenic activities, thus lowering the assay time to half or less than what was previously reported (3,5). In this study, we also examined the effect of cysteine HC1…”
Section: Discussionmentioning
confidence: 83%
“…The murine hybridoma Ped-2E9 cell line was produced by the fusion of murine myeloma NS 1 (TIB 18, ATCC, Rockville, Md., U.S.A.) and splenocytes from mice that were immunized with Pediococcus acidilacti- (3,5). Briefly, the hybridoma cells (2 X 106/m1) were inoculated with bacteria at a multiplicity of infection of 100 bacteria to 1 hybridoma cell, and incubated at 37 C. Ped-2E9 cells (0.1 ml) were withdrawn at specified times, stained with trypan blue (0.4%) and counted under a microscope.…”
Section: Methodsmentioning
confidence: 99%